As mulheres na política brasileira: um estudo sob a perspectiva sistêmico-funcional - Morais, Fernanda Beatriz Caricari de (2008)
This study aims to analyze the representation of women politicians in articles from magazines like Veja, Época and IstoÉ. Linguistics Functional Grammar of Halliday (1994, 2004) and followers (Eggins, 1994, Thompson, 1996) was used to analyze the ideational metafunction, so as to characterize the use of the language as representation. The studies as Grossi e Miguel (2001) and Avelar (2001) were used as a support to analyze the data and to understand the role of women in Brazilian politics. The data were collected from the magazines websites and separated in two corpora: women politician and men politician. They both were submitted to the software WordSmith Tools (Scott, 1998) and to the tools it offers, such as Concord and WordList used to assist the linguistic analyzes. Results show that although Brazil had many social and politics changes, women and men had different representations. Many times, women are represented by their private lives and their female characteristics and not by their professional characteristics and competence. Men are represented by their competition and dishonesty. The present work intends to have contributed to the analysis of the importance of women participation in politics and their role in society